Pengembangan Aplikasi Evaluasi Kegiatan Berbasis Android menggunakan Metode RAD (Rapid Application Development) - Egia Rosi Subhiyakto; Feri Agustina; Charesta Vida Reswara (Universitas Muhadi Setiabudi, 2023)
The development of technology is very fast, especially in the field of information systems. Companies, organizations, schools and governments definitely need the role of information technology in data security or management. The use of the internet is very much needed in government agencies because the internet is used as a means to provide fast and easy services to people who want to handle important documents. In this research, we developed an Android-based application to evaluate activities have been carried out. We named this application EL-AKIP which is an android-based application for Grobogan Regency designed using web 2.0 and restful api using the RAD (Rapid Application Development) method. The use of Rapid Application Development (RAD), which is a software development process model that is incremental, especially for short processing times. Application testing uses the black box testing method where the results show that the application passes the test and is feasible to use